IOT-based power control systems framework for healthcare applications. (February 2023) - Priyadarshini, R.; Shaikh, Naim; Godi, Rakesh Kumar; Dhal, P.K.; Sharma, Rajeev; Perwej, Yusuf
Abstract: Battery-powered EGC systems are improved with different IoT mechanisms in particular for the treatment of cardiovascular problems. To extend the battery capacity of IoT devices in the ECG monitoring system, an energy-saving technique was adopted using the VLSI design have been given in this study. The proposed power control computer automatically switches between two modes of transmission, i.e., greater style of power and reduced power, style, according to the battery intensity. A light approach stressing slope augmentation with a real-time segmentation algorithm was proposed for QRS complex assessment of pulse rate, guaranteeing optimum energy consumption during low battery capacity because on-node localized computation was a source of energy. Proper power transmission mode was chosen to efficiently achieve the objectives of the Wireless Body Area Network (WBAN) device, gathering sufficient ECG data from a specific patient and will increase in the charging level of the entire system with pulse rate consistency. The MIT-BIH arrhythmias dataset was used to assess the sensitivity. The design was suited for real-time ECG surveillance systems because it has been developed in a Spartan6 FPGA with a maximum frequency of 269 MHz and energy consumption of 0.7 MW.